Invivo and in vitro analyses of surface whitening in hydrophobic trifocal intraocular lenses - Cabanás, Margarita; Navalón, Jorge; Luchena, Rafael; Lee, William; Cerviño, Alejandro (Frontiers in Medicine, 2025)
IntroductionTransparency loss due to the whitening of trifocal hydrophobic intraocular lenses (IOLs) is a rare but poorly understood phenomenon. This study investigates its characteristics, underlying mechanisms, and clinical impact to determine its relevance for patient care.MethodsA clinical and laboratory analysis was conducted on affected IOLs. Two patients with bilateral trifocal IOL implantation, where one eye exhibited whitening, underwent visual performance testing, light distortion assessment, optical coherence tomography, Scheimpflug imaging, and patient-reported outcome evaluations. An explanted IOL was examined using microscopic and optical bench methods, and attempts were made to replicate the whitening process in vitro using unused control lenses.ResultsClinical findings showed that IOL whitening had minimal impact on visual acuity and light distortion, with no significant impairment reported in patient-reported outcomes. Imaging and laboratory analysis suggested that whitening is caused by subsurface nanoglistening (SSNG), a previously unreported phenomenon in this IOL material. The modulation transfer function of the affected IOLs remained comparable to control lenses, and in vitro attempts to induce whitening were unsuccessful.DiscussionThis study provides the first evidence of SSNG in this hydrophobic IOL material, demonstrating that while whitening can occur, its clinical significance is generally low. Given the predominantly subjective nature of symptoms, management should be individualized, with explantation decisions made in close consultation with the patient. These findings contribute to a better understanding of IOL material stability and patient counseling in cases of transparency loss.